ACTUALITY OF TWINS UPBRINGING/SELF-UPBRINGING IN CONTEMPORARY SOCIETY - Dumbrauska, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In this research the culture history methodology approach has been used for the research of theoretical sources on upbringing/self-upbringing correlations. The objective and subjective factors influencing upbringing/self-upbringing characterizing the individual twins personality have been defined and given the analysis of the correlated components: temperament, attitudes, abilities, volition. The upbringing fosters self-upbringing, where volition and goal-directed action serve as the development opportunity for human abilities, while the twins  individuality  fostering techniques (undertaking of commitments, self-analysis, self-reporting, self-control, self-assessment) provide an opportunity to each child for self-upbringing, independent choice by herself/himself, autonomous action and the responsibility for the results of her/his own individual self-upbringing. The research drew the conclusions that  development and enhancement of each twin's freedom, autonomy and responsibility is fostered by  upbringing/ self-upbringing.  By scientific literature research, each twin's individuality upbringing criteria (independent choice, autonomy and responsibility) were studied, thus, providing opportunity for further research of the twin's  individuality upbringing dynamics in practice.